2003
DOI: 10.1177/073953290302400107
|View full text |Cite
|
Sign up to set email alerts
|

Newspapers Slow to Use Web Sites for 9/11 Coverage

Abstract: This analysis of 89 U.S. daily newspaper Web sites on Sept. 11, 2001, shows that 65 percent of the home pages in the late morning and 38 percent in the late afternoon said nothing about the World Trade Center bombings. By late afternoon only 43 percent of the home pages had at least one photo or video of the 9/11 attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The web editions with more internet features than the rest tended to belong to the newspapers with larger circulations than the rest. This, too, is consistent with studies of web newspapers elsewhere in Asia (Massey, 2000) and in the US (Greer and Mensing, 2004;Randle et al, 2003;Schultz, 1999;Tankard and Ban, 1998;Weiss, 2004), although few of them tested theory.…”
Section: Discussionsupporting
confidence: 85%
“…The web editions with more internet features than the rest tended to belong to the newspapers with larger circulations than the rest. This, too, is consistent with studies of web newspapers elsewhere in Asia (Massey, 2000) and in the US (Greer and Mensing, 2004;Randle et al, 2003;Schultz, 1999;Tankard and Ban, 1998;Weiss, 2004), although few of them tested theory.…”
Section: Discussionsupporting
confidence: 85%
“…This refers to the implementation of immediacy and how immediacy makes its mark on the actual content of the news. Randle et al (2003) found that 89 US daily newspapers were very slow to update their websites with information about the 9/11 attack, not fully using the medium's potential for immediacy.…”
Section: Researching Immediacy: Producers Consumers and Contentmentioning
confidence: 99%